2019
DOI: 10.1007/s41109-019-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

A multi-armed bandit approach for exploring partially observed networks

Abstract: Background: real-world networks such as social and communication networks are too large to be observed entirely. Such networks are often partially observed such that network size, network topology, and nodes of the original network are unknown. Analysis on partially observed data may lead to incorrect conclusions. Methods: We assume that we are given an incomplete snapshot of a large network and additional nodes can be discovered by querying nodes in the currently observed network. The goal of this problem is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“… 18 , 21 , 65 , 66 In an in principle infinite chemical space, another central AML design choice regards the extent over which new molecules are practically assessed with the established, conceptually global surrogate model. Aiming for high-performance OSC molecules of tractable size and complexity, we here opt for a single tree expansion that limits the candidates to those in the vicinity of already sampled ones 67 .…”
Section: Resultsmentioning
confidence: 99%
“… 18 , 21 , 65 , 66 In an in principle infinite chemical space, another central AML design choice regards the extent over which new molecules are practically assessed with the established, conceptually global surrogate model. Aiming for high-performance OSC molecules of tractable size and complexity, we here opt for a single tree expansion that limits the candidates to those in the vicinity of already sampled ones 67 .…”
Section: Resultsmentioning
confidence: 99%
“…An important observation is that immediate contacts alone (as done in previous work (e.g., Singla et al 2015, Soundarajan et al 2017, Madhawa and Murata 2019)) may be insufficient to consider for COVID-19 testing and we need a richer representation of similarity between individuals. We seek to model similarity such that if one agent is infected, then a similar node is also possibly infected.…”
Section: Active Sampling Framework and Algorithmmentioning
confidence: 99%
“…Beyond classic bandit problems, there exists literature on active search, with the objective of finding as many target nodes as possible with some given property. Most of the existing work assumes that the complete network structure is known before hand (e.g., Ma et al 2015), with the exception of a few recent papers that consider partially observed networks (e.g., Singla et al 2015, Soundarajan et al 2017, Madhawa and Murata 2019). However these approaches do not consider the node sampling scenario needed for the testing problem considered in this paper.…”
Section: Active Sampling Framework and Algorithmmentioning
confidence: 99%
“…Murai et al (2018) propose a multi-armed bandit algorithm for reducing network incompleteness that probabilistically chooses from an ensemble of classifiers that are trained simultaneously. Madhawa and Murata (2019) describe a nonparametric multi-armed bandit based on a k-nearest neighbor upper-confidence bound algorithm, which will be described in more detail in Experiments section.…”
Section: Related Workmentioning
confidence: 99%